Alternatively folded proteins with unexpected beneficial functions. (20th July 2012) - Min, Soyoung; Meehan, James; Sullivan, Louise M.; Harte, Níal P.; Xie, Yongjing; Davey, Gavin P.; Svanborg, Catharina; Brodkorb, André; Mok, K. Hun
Abstract : HAMLET (human α-lactalbumin made lethal to tumour cells) and its related partially unfolded protein–fatty acid complexes are novel biomolecular nanoparticles that possess relatively selective cytotoxic activities towards tumour cells. One of the key characteristics is the requirement for the protein to be partially unfolded, hence endowing native proteins with additional functions in the alternatively folded states. Beginning with the history of its discovery and development, the cellular targets that appear to be strongly correlated with tumour cell death are introduced in the present article.